Positif Ageing Sebagai Counter Hegemony Ageism Dalam Film “The Intern” - Andini Ekanesia Putri (Jurnal Ilmu Komunikasi, 2021)
Film as a popular communication medium is expected to represent the feelings of its audience in a story or issue raised. As with other gender issues, issues regarding aging and ageism also deserve to be raised in a big story. But in reality, this is very rarely done by local and foreign filmmakers. One of the films that can represent the issue of aging well is the film “The Intern” which illustrates that the process of aging or aging itself is not as scary as what has been constructed by social society. The fear of the aging and aging process makes people look anti to this natural process and even hate it. This behavior gives rise to the ideology of ageism which is able to limit the movement of the elderly group and can be included as training for the elderly group. Positive aging which is an attitude of looking positively at the aging process is considered as a resistance to an attitude of hatred towards the aging process or what can be called ageism.